Practice, instruction and skill acquisition in soccer: Challenging tradition - Williams, A. M.; Hodges, N. J. (Journal of Sports Sciences, 2005)
The acquisition of soccer skills is fundamental to our enjoyment of the game and is essential to the attainment of expertise. Players spend most of their time in practice with the intention of improving technical skills. However, there is a lack of scientific research relating to the effective acquisition of soccer skills, especially when compared with the extensive research base on physiological aspects of performance. Current coaching practice is therefore based on tradition, intuition and emulation rather than empirical evidence. The aim of this review is to question some of the popular beliefs that guide current practice and instruction in soccer. Empirical evidence is presented to dispel many of these beliefs as myths, thereby challenging coaches to self-reflect and critically evaluate contemporary doctrine. The review should inform sports scientists and practitioners as to the important role that those interested in skill acquisition can play in enhancing performance at all levels of the game.